Cultural intelligence a guide to working with people from other cultures - Peterson, Brooks (Intercultural Press, 2004)
Packed with dozens of engaging stories, case studies and humorous contemporary cartoons, Cultural Intelligence is the perfect antidote for overcoming cross-cultural differences, improving workplace communication and building solid business relationships. Using a set of twenty business-oriented dimensions, Dr. Peterson helps you examine your own cultural style and determine that of others in six vital areas: management, strategy, planning, personnel, communication and reasoning.